Lexical, syntactic and semantic language processes and spelling performance in 5th and 6th grade primary school students: neuropsychological cognitive approach - Dioses Chocano, Alejandro (2014)
The study explored, from the cognitive neuropsychological perspective, the spelling performance of boys and girls in 5° and 6° primary school, between 10 and 11 years old, attending public and private schools in Lima. The research was descriptive with a non - experimental –transeccional– descriptive design, used as an instrument, the Spelling Test Performance (PRO), levels 1-2, which has a 0.90 reliability and structural validity ranging from 0.523 (semantic processing) to 0.902 (lexical processing). We globally found, that men and women didn't showed significant differences in the spelling performance, although girls achieved significantly better performance on tests of punctuation marks, exclamation and interrogation marks, while males showed a performance significantly better on the test of accent marks. On the other hand, sixth grade students, compared to fifth graders, only showed significant difference in the punctuation test; otherwise happening in homophones test dictation.